Characteristics of immune cell infiltration and associated diagnostic biomarkers in ulcerative colitis: results from bioinformatics analysis. Issue 1 (1st January 2021) - Xue, Guohui; Hua, Lin; Zhou, Nanjin; Li, Junming
ABSTRACT: Ulcerative colitis (UC) is a type of refractory and recurrent inflammatory disorder that occurs in colon and rectum. Immune cell infiltration plays a critical role in UC progression; therefore, this study aims to explore potential biomarkers for UC and to analyze characteristics of immune cell infiltration based on the bioinformatic analysis. In this study, 248 differentially expressed genes (DEGs) were screened, and the top 20 immune-related hub genes and pathways were assessed. Moreover, four candidate diagnostic biomarkers (DPP10, S100P, AMPD1, and ASS1) were identified and validated. Immune cell infiltration analysis identified 13 differentially infiltrated immune cells (IICs) in UC samples compared to normal samples, and the result showed that two IICs only expressed in UC samples. In addition, the present research found that DPP10 was negatively correlated with neutrophils, S100P exhibited a positive correlation with resting CD4 memory T cells, AMPD1 was positively correlated with M2 macrophages, and ASS1 was inversely associated with neutrophils and positively related to CD8 T cells. Taken together, these findings indicated that DPP10, S100P, AMPD1, and ASS1 may act as diagnostic biomarkers for UC, and that differential IICs may help to illustrate the progression of UC. Graphical Abstract: uf0001